Melek Media: Strategi Pencegahan Pengaruh Buruk Media Televisi pada Anak-anak - FRIZKY YULIANTI NURNISYA (Komunikator, 2013)
Television gives significant impact to the audience especially children. Some theories of mass communication show how strong the relationship between television and the audience is. In Indonesia, there are some cases about imitating violent of television programs which are caused by the publication of mass media. In order to decrease the bad influence from television, mediation by the parents is essential so that children do not get bad influence by the use of media literacy. Keywords: mediation, television, children